Daya Dukung Regulagi Terhadap Kebijakan Circular Economic Sebagai Realisasi Pembangunan Berkelanjutan (Sustainable Development Goals/SDGS) di Indonesia - Utami, Tanti Kirana; Ramadani, Azzahara Salsabila; Permatasari, Ira; Azzahra, Najmah Fatimah; Hujaipah, Wanda; Yarico, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
There are several concepts to overcome waste problems through recycling, namely open dumping, zero waste, and circular economy. For zero waste or no waste is a philosophy that encourages the redesign of the resource cycle, from a linear system to a closed cycle, where the author uses a normative juridical law research method that is prescriptive, namely practical or applied and aims to solve problems. The research approach used by the author includes a statute approach, and a conceptual approach that uses primary legal materials, secondary legal materials to solve the subject matter related to the law that regulates the problem of recyclable waste.